10.1001/TESTjama.2012.6380 (CrossRef Listing of Deleted DOIs, 2000)
Importance Mobile integrated health (MIH) is a promising model for improving transitions of care for patients with heart failure (HF). National implementation remains limited due to insufficient understanding of barriers and facilitators to adoption and sustainability. Objective To identify factors associated with the implementation of an MIH program for patients with HF in an urban setting, using the Reach, Effectiveness, Adoption, Implementation, Maintenance (RE-AIM) framework. Design, setting, and participants This qualitative study was embedded in the Using Mobile Integrated Health and Telehealth to Support Transitions of Care Among Heart Failure Patients (MIGHTy-Heart) randomized clinical trial conducted from January 2021 to September 2024 at 2 large urban health systems in New York, New York. Qualitative data were generated through semistructured interviews with patients and stakeholders (clinicians, paramedics, caregivers, and program leaders). Data were analyzed from January 2022 through August 2023. Exposure The MIH intervention included home visits from community paramedics, ongoing nurse care coordination, and facilitated telehealth consultations. Main outcomes and measures Five RE-AIM domains were assessed using directed content analysis of interview data. Quantitative reach was measured by comparing adults with HF offered access to MIH to all adults with HF receiving care at the health systems during the study period, and effectiveness data were summarized descriptively from the parent MIGHTy-Heart trial. Adoption was measured by comparing facilitators and barriers to adoption. Implementation was assessed through service utilization and thematic analysis. Maintenance included willingness to recommend MIH and institutional continuation plans. Results A total of 73 343 patients (51 420 [70%] aged ≥65 years; 39 979 [55%] male) were treated for HF across both health systems during the trial period, including 1005 who were enrolled in the trial and randomized to MIH, among whom 414 received at least 1 MIH visit; 20 patients and 25 stakeholders were interviewed for qualitative results. Regarding reach, MIH participants vs all patients with HF were similar with respect to age and sex, but had greater racial and ethnic diversity (MIH group: 50% Black or African American, 27% Hispanic or Latino, and 25% White; all HF patients: 9% Black or African American, 4% Hispanic or Latino, and 42% White). Regarding effectiveness, there was no statistically significant decrease in 30-day all-cause readmissions or Kansas City Cardiomyopathy Questionnaire scores among MIH participants vs the comparator group (mean difference, 1.83; 95% CI, -0.75 to 4.40; P = .16). Adoption was promoted by institutional alignment, and implementation was supported by leadership engagement, interdisciplinary coordination, and patient trust. Barriers included misaligned reimbursement and regulatory constraints. Sustainability plans reflected MIH's perceived value to patients and staff. Conclusions and relevance Despite the primary trial showing no difference in 30-day readmissions or Kansas City Cardiomyopathy Questionnaire scores between MIH and the transitions of care coordinator control group, this qualitative study found that MIH was well received and aligned with institutional goals. Sustaining and scaling MIH may require supportive reimbursement models and policy reforms.